Biomechanical and bioenergetical evaluation of swimmers using fully-tethered swimming: A qualitative review - Amaro, N. M.; Morouço, P. G.; Marques, M. C.; Fernandes, R. J.; Marinho, D. A. (Journal of Human Sport & Exercise, 2017)
It is presented a qualitative review of the specialized literature on fully-tethered swimming, with the scopes of summarizing and highlighting published knowledge, identifying its gaps and limitations, and motivate future research. The major research conclusions can be summarized as follows: (i) tethered swimming is a reliable test to evaluate force exerted in water by swimmers; (ii) higher maximum values of force are obtained in breaststroke and butterfly, while average values are higher in front crawl; (iii) tethered forces present moderate to strong relationships with swimming velocity, and associations between forces diminish as swimming distance increases; (iv) 30 s maximal tethered swimming may be used as an adaptation of Wingate test for swimming; (v) differences in stroke mechanics can occur in tethered swimming but there is no evidence to suggest that they affect swimming performance; (vi) Tethered swimming is a valid methodology to evaluate aerobic energy contribution in swimming and recent investigations concluded that it can also provide information on the anaerobic contribution. Based on and stimulated by current knowledge, further research should focus on the following topics: (i) the usefulness of tethered swimming as a valid tool to evaluate other swimming techniques; (ii) differences in force parameters induced by gender or competitive level; (iii) defining accurate variables for estimation of anaerobic power and/or capacity using tethered swimming; (iv) bilateral asymmetries in exerted forces, and corresponding influence of breathing; (v) relative contribution of arms and legs for whole-body propelling forces.